Transdiagnostic brain responses to disorder-related threat across four psychiatric disorders. Issue 4 (21st November 2016) - Feldker, K.; Heitmann, C. Y.; Neumeister, P.; Tupak, S. V.; Schrammen, E.; Moeck, R.; Zwitserlood, P.; Bruchmann, M.; Straube, T.
Abstract : Background: There is an ongoing debate whether transdiagnostic neural mechanisms are shared by different anxiety-related disorders or whether different disorders show distinct neural correlates. To investigate this issue, studies controlling for design and stimuli across multiple anxiety-related disorders are needed. Method: The present functional magnetic resonance imaging study investigated neural correlates of visual disorder-related threat processing across unmedicated patients suffering from panic disorder ( n = 20), social anxiety disorder ( n = 20), dental phobia ( n = 16) and post-traumatic stress disorder ( n = 11) relative to healthy controls (HC; n = 67). Each patient group and the corresponding HC group saw a tailor-made picture set with 50 disorder-related and 50 neutral scenes. Results: Across all patients, increased activation to disorder-related v . neutral scenes was found in subregions of the bilateral amygdala. In addition, activation of the lateral amygdala to disorder-related v . neutral scenes correlated positively with subjective anxiety ratings of scenes across patients. Furthermore, whole-brain analysis revealed increased responses to disorder-related threat across the four disorders in middle, medial and superior frontal regions, (para-)limbic regions, such as the insula and thalamus, as well as in the brainstem and occipital lobe. We found no disorder-specific brain responses. Conclusions: The results suggest that pathologically heightened lateral amygdala activation is linked to experienced anxiety across anxiety disorders and trauma- and stressor-related disorders. Furthermore, the transdiagnostically shared activation network points to a common neural basis of abnormal responses to disorder-related threat stimuli across the four investigated disorders.